Chinese Herbal Medicines Attenuate Acute Pancreatitis: Pharmacological Activities and Mechanisms - Xiang, Hong; Zhang, Qingkai; Qi, Bing; Tao, Xufeng; Xia, Shilin; Song, Huiyi; Qu, Jialin; Shang, Dong (Frontiers in Pharmacology, 2017)
Abstract Acute pancreatitis (AP) is a commonly occurring gastrointestinal disorder. An increase in the annual incidence of AP has been observed, and it causes acute hospitalization and high mortality. The diagnosis and treatment guidelines for AP recommend conservative medical treatments focused on reducing pancreatic secretion and secondary injury, as a primary therapeutic approach. Unfortunately, the existing treatment options have limited impact on the incidence and severity of AP due to the complex and multifaceted pathological process of this disease. In recent decades, Chinese herbal medicines (CHMs) have been used as efficient therapeutic agents to attenuate AP in Asian countries. Despite early cell culture, animal models, and clinical trials, CHMs are capable of interacting with numerous molecular targets participating in the pathogenesis of AP; however, comprehensive, up-to-date communication in this field is not yet available. This review focuses on the pharmacological activities of CHMs against AP in vitro and in vivo and the underlying mechanisms. A computational prediction of few selected and promising plant-derived molecules (emodin, baicalin, resveratrol, curcumin, ligustrazine and honokiol) to target numerous proteins or networks involved in AP was initially established based on a network pharmacology simulation. Moreover, we also summarized some potential toxic natural products for pancreas in order to more safe and reasonable medication. These breakthrough findings may have important implications for innovative drug research and the future development of treatments for AP.